Regulasi Emosi Terhadap Pencegahan Tindakan Agresif pada Remaja: Studi Literatur - Deso, Maria Celina Jama; Rohi, Enasely Mega Wenyi (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to determine the relationship between emotional regulation and the prevention of aggressive behavior in adolescents. The method used is a literature review by examining various scientific sources such as journals, books, and relevant previous research results. The results of the study show that emotional regulation has a negative relationship with aggressive behavior, where the better an individual's ability to manage their emotions, the lower their tendency to engage in aggressive acts, whether physical, verbal, or social. These findings emphasize the importance of strengthening emotional regulation skills in adolescents to prevent aggressive behavior in educational.